A statistical comparison of flood-related economic damage in Indian states with reflections on policy implications. (1st April 2022) - Das, Sourav; Sheth, Arshay Nimish; Bansal, Priya; Chuah, Joon; Wasson, Robert
Abstract: Economic damage caused by floods in India is a serious problem that has disrupted development and the fight against poverty in some parts of the country. It is therefore important to mitigate the effects of floods as effectively as possible. An analysis of aggregated economic damage in the categories of crops, housing and utilities in six Indian States from 1953 to 2011 is presented using rigorous statistical methods. The main result is that increasing mitigation efforts since Independence have not produced a monotically decreasing long term trend in damage, although the magnitude of reduction cannot be known precisely, based on publicly available data. Andhra Pradesh has the highest total damage followed by Bihar, West Bengal, Orissa, Assam, and Gujarat. The reasons for this ranking are unclear because the only publicly available proxy for potential damage, has a weak statistical effect. Similarities in damage between some States suggest that inter-State learning may be of value despite differences in hydrology, landscape and economic activity. Despite the deficiencies in the data and its spatial resolution, there is sufficient evidence to inspire new thinking and action about flood mitigation in India, for which District and Taluk level data will be essential.